2008
DOI: 10.1109/jqe.2008.2002104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quantum Well Compressive Strain Above 1% On Differential Gain and Threshold Current Density in Type-I GaSb-Based Diode Lasers

Abstract: Abstract-InGaAsSb/AlGaAsSb quantum well (QW) diode laser structures with either 1% or 1.5% compressively strained QWs were grown on GaSb substrates by molecular beam epitaxy. Widestripe lasers fabricated from structures of both types have roomtemperature operating wavelengths near 2.3 microns. The roomtemperature threshold current density of 1-mm-long uncoated devices with 1.5% strained QWs was lower than threshold current density of the 1.0% strained QW devices by nearly a factor of two (120 A/cm 2 versus 230… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 19 publications
(17 reference statements)
0
25
0
Order By: Relevance
“…In mid-infrared GaInAsSb devices, carrier leakage occurs mainly through the valence band due to the small valence band offset between the quantum well and barrier layers. Improved carrier confinement has been achieved independently, with both increased levels of compressive strain, and through the larger valence band offset offered by quinternary AlGaInAsSb barriers [17], [18]. Improvements in carrier confinement has been the main pathway in achieving room temperature and CW operation well above 3 μm.…”
Section: Introductionmentioning
confidence: 99%
“…In mid-infrared GaInAsSb devices, carrier leakage occurs mainly through the valence band due to the small valence band offset between the quantum well and barrier layers. Improved carrier confinement has been achieved independently, with both increased levels of compressive strain, and through the larger valence band offset offered by quinternary AlGaInAsSb barriers [17], [18]. Improvements in carrier confinement has been the main pathway in achieving room temperature and CW operation well above 3 μm.…”
Section: Introductionmentioning
confidence: 99%
“…High power GaSb-based diode lasers have been reported in this spectral region [1]- [9]. Studies on the role of compressive strain above 1% on the threshold and efficiency of GaSb-based diode lasers have been performed [10], [11]. It was demonstrated that increasing the compressive strain from 1 to 1.5% in GaInAsSb QWs improves both the differential gain and the threshold current density of diode lasers.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of the compressive strain was previously identified as an effective way to improve hole confinement in QWs. 2 The barrier and waveguide material was the quinary AlInGaAsSb alloy lattice-matched to GaSb. The use of the quinary In-containing material as QW barriers also improves hole confinement.…”
Section: Diode Lasers Operating At Rt In the 3-35 μπι Spectral Rangementioning
confidence: 99%
“…In QWs compressively strained above 1%, the top valence subband has an in-plane effective mass that is rather close to electron effective mass. 2 The resulting reduced density of states facilitates separating the quasi-Fermi levels in narrow bandgap active QWs under injection. Since bulk transition matrix element does not show pronounced material bandgap dependence, 1 this leads to improved differential gain in narrow bandgap QWs.…”
Section: Introductionmentioning
confidence: 99%